Identifying UiTM Penang Faculty of Hotel Management and Tourism students’ needs in English language proficiency (verbal communication skills) / Farina Nozakiah Tazijan, Suzana Ab. Rahim, Aznizah Hussin - Tazijan, Farina Nozakiah; Ab. Rahim, Suzana; Hussin, Aznizah (2009)
There is a need to expose the learners in the hospitality industry to real workplace requirement in terms of communication skills. In view of its importance, human resource managers, researchers and educators in the field of hospitality management or the hotel practitioners have to pay more serious attention to it. Thus, it is pertinent that both employers and potential employees have a consensus on what are to be instilled in the learners as this would prepare them for the actual hotel reception practices which in particular are the verbal communication skills. This study looks at both the employers’ and employees’ perceptions and expectations of the communication skills required by the profession. A needs analysis in the form of a questionnaire, distributed to the hotel managers and the interns involved help to identify the verbal communication skills that the interns seem to require. The results highlight the views of employers in identifying the needs and lacks of the interns under their supervision. In bridging the gap of communication skills expected by the hospitality industry and the competence or ability of the interns, it is of priority that the lacks and needs of these interns be looked into. This study also has identified the students’ perceptions of their language needs, wants and lacks in the verbal communication skills so as to prepare them for their real world workplace requirement This knowledge is hoped to assist the curriculum designers in producing future hotel management professionals that can function effectively at their workplace.